KAJIAN IKONOGRAFI KARYA DULLAH â€œPRAKTIK TENTARA PENDUDUKAN ASINGâ€ - Adisukma, Wisnu (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2015)
The article tittled The Iconography of Dullah’s artwork "Foreign Occupation Soldiers Practice" is intended to seek the textual and contextual meaning of Dullah’s art work. With iconographic approach will be obtained deeper and broader meaning from a work of art. Through this approach, the artwork will be a major concern in reviewing the history of art, nevertheless also necessary to understand the contextual and symbolic aspects. At the time of independence Dullah documentating the events related to the struggle of the Indonesian nation to seize and retain independence in his works. Dullah even led a group of young artists to paint directly of events during the occupation of Yogyakarta as an effort to document the history of the struggle of the nation. One of his very famous is"Foreign Occupation Soldiers Practice". This work depicts the atrocities of the Japanese army against the population Indonesia. It is a very strong art work is the "Foreign Occupation Soldiers Practice" that depicts cruelty colonizers against the indigenous population. In this case the work of "Foreign Occupation Soldiers Practice" finds its context as understood by tracing the socio-cultural history during the years 1930-1940. From the art work we can find out how the socio-historical situation of the community when the colonial era. Keywords :Dullah, Iconography, Praktik Tentara Pendudukan Asing.